Climatology of contribution‐weighted tropical rain rates based on TRMM 3B42. Issue 19 (6th October 2016) - Venugopal, V.; Wallace, J. M.
Abstract: The climatology of annual mean tropical rain rate is investigated based on merged Tropical Rainfall Measuring Mission (TRMM) 3B42 data. At 0.25° × 0.25° spatial resolution, and 3‐hourly temporal resolution, half the rain is concentrated within only ∼1% of the area of the tropics at any given instant. When plotted as a function of logarithm of rain rate, the cumulative contribution of rate‐ranked rain occurrences to the annual mean rainfall in each grid box is S shaped and its derivative, the contribution‐weighted rain rate spectrum, is Gaussian shaped. The 50% intercept of the cumulative contribution R 50 is almost equivalent to the contribution‐weighted mean logarithmic rain rate R L ¯ based on all significant rain occurrences. The spatial patterns of R 50 and R L ¯ are similar to those obtained by mapping the fraction of the annual accumulation explained by rain occurrences with rates above various specified thresholds. The geographical distribution of R 50 confirms the existence of patterns noted in prior analyses based on TRMM precipitation radar data and reveals several previously unnoticed features. Key Points: A new metric, contribution‐weighted rain rate, is proposed to characterize the climatology of tropical rain At 0.25° × 0.25° resolution, and 3‐hourly temporal resolution, half the rain falls in 1% of the area of the tropics The spectrum of contribution‐weighted rain rate is nearly lognormal